Need Assesment Anak Berkebutuhan Khusus di Sekolah Terintegrasi - Opi Andriani; Arvivi Suriyanti; Febri Andika (Badan Penerbit STIEPARI Press, 2024)
The purpose of this study is to determine the Need Assessment of Children with Special Needs in Integrated Schools. Children with special needs often face challenges when it comes to learning and interacting in a typical school environment. In an effort to ensure that their needs are well met, it is necessary to conduct a thorough assessment to identify their individual special needs. This study used a qualitative method involving participants from students, teachers, parents, and integrated school staff at SDN 31/II Bangun Jayo.